Impacts of Ocean Warming on Coralline Algal Calcification: Meta-Analysis, Knowledge Gaps, and Key Recommendations for Future Research - Cornwall, Christopher E.; Diaz-Pulido, Guillermo; Comeau, Steeve (Frontiers in Marine Science, 2019)
Coralline algae are foundation species in many hard-bottom ecosystems acting as a settlement substrate, and binding together and even creating reefs in some locations. Ocean acidification is known to be a major threat to coralline algae. However, the effects of ocean warming are less certain. Here we bring multiple lines of evidence together to discuss the potential impacts of ocean warming on these ecologically crucial taxa. We use a meta-analysis of 40 responses within 14 different studies available which assessed the effects of increasing temperature on coralline algal calcification in laboratory experiments. We find a net negative impact of increasing temperature on coralline algal calcification at 5.2°C above ambient conditions. Conversely, negative effects are observed when temperature drops below 2.0°C from ambient conditions. We propose that some coralline algae will be more capable of both acclimatizing and locally adapting to increasing ocean temperatures over the coming decades. This is because many species possess short generation times, the ability to opportunistically rapidly utilize open space, and relatively high phenotypic plasticity. However, less resistant and resilient species will be those that are long-lived, those with long generation times, or with narrow thermal tolerances (e.g., tropical taxa living close to their thermal maxima). Additionally, ocean warming will occur simultaneously with ocean acidification, a potentially greater threat to coralline algae, which could also reduce any tolerance to ocean warming for many species. To maximize the potential to accurately determine how coralline algae will respond to future ocean warming and marine heatwaves, future research should use environmentally relevant temperature treatments, use appropriate acclimation times and follow best practices in experimental design.